Neo-Victorian villains : adaptations and transformations in popular culture - Poore, Benjamin, 1971- (Leiden, The Netherlands ; Boston : Brill, 2017)
Neo-Victorian Villains is the first edited collection to examine the afterlives of such Victorian villains as Dracula, Svengali, Dorian Gray and Jekyll and Hyde, exploring their representation in neo-Victorian drama and fiction. In addition, Neo-Victorian Villains examines a number of supposedly villainous types, from the spirit medium and the femme fatale to the imperial 'native' and the ventriloquist, and traces their development from Victorian times today. Chapters analyse recent theatre, films and television - from Ripper Street to Marvel superhero movies - as well as classic Hollywood depictions of Victorian villains. In a wide-ranging opening chapter, Benjamin Poore assesses the legacy of nineteenth-century ideas of villains and villainy in the twentieth and twenty-first centuries. Contributors are: Sarah Artt, Guy Barefoot, Jonathan Buckmaster, David Bullen, Helen Davies, Robert Dean, Marion Gibson, Richard Hand, Emma James, Mark Jones, Emma V. Miller, Claire O'Callaghan, Christina Parker-Flynn, Frances Pheasant-Kelly, Natalie Russell, Gillian Piggott, Benjamin Poore and Rob Welch.
The Villain-Effect: Distance and Ubiquity in Neo-Victorian Popular Culture / Benjamin Poore -- Theatrical Transformations -- 'A Perfect Demon': Michael Eaton's Charlie Peace: His Amazing Life and Astounding Legend / Richard J. Hand -- Miss Representation: The Femme Fatale and the Villainy of Performance in Neo-Victorian Hollywood / Christina Parker-Flynn -- Melodramatic Villainy (Just) after the Victorians / Guy Barefoot -- Imperial Heroes and Native Villains / Robert Dean -- Sonorous Psychopaths: Neo-Victorian Ventriloquists on Screen / Gillian Piggott -- Transitional and Liminal Figures -- Kissing the Medium: The Spiritualist-Witch as Countercultural Heroine in The Thirty-Nine Steps (1959) / Marion Gibson -- Jack the Representation: The Ripper in Culture / Mark Jones -- On the Origin of a Supervillain: The Neo-Victorian Reinvention of Mister Sinister / David Bullen -- Framing Our Fearful Symmetry: Substance Dualism, Reincarnation and the Villainy of the Disembodied Soul / Emma V. Miller -- Neo-Victorian Sex and 'Sexsation' -- The Postfeminist Tart: Neo-Victorian Villainy and Sex Work in Ripper Street / Sarah Artt -- "I raise the devil in you, not any potion. My touch": The Strange Case of Heterosexuality in Neo-Victorian Versions of Jekyll and Hyde / Helen Davies -- A Wilde Scoundrel: Villainy and 'Lad Culture' in the Filmic Afterlives of Dorian Gray / Claire O'Callaghan -- Literary Villains Reimagined -- Svengali: The Evolution of Ethnic Evil through Adaptation / Rob Welch -- From 'the wicked man' to the 'bastard boy of seven': The Evolution of John Jasper's Villainy in Adaptations of The Mystery of Edwin Drood / Jonathan Buckmaster -- "I'm always angry": Super-Hydes and the Appropriation of Edward Hyde in Superhero Films / Emma A. Harris -- Revisionist Vampires: Transcoding, Intertextuality, and Neo-Victorianism in the Film Adaptations of Bram Stoker's Dracula / Frances Pheasant-Kelly and Natalie Russell.
Includes index.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on August 10, 2017).
eBooks on EBSCOhost
Keywords: Villains in literature; Villains in motion pictures; Characters and characteristics in literature; Characters and characteristics in motion pictures; English literature -- Adaptations -- History and criticism; English literature -- 19th century -- Influence; Méchants dans la littérature.; Méchants au cinéma.; Personnages au cinéma.; Littérature anglaise -- 19e siècle -- Influence; 1800-1899.; LITERARY CRITICISM / European / English, Irish, Scottish, Welsh; Characters and characteristics in literature; Characters and characteristics in motion pictures; English literature -- Influence; Villains in literature; Villains in motion pictures; 1800-1899; Criticism, interpretation, etc